2016
DOI: 10.1002/atr.1372
|View full text |Cite
|
Sign up to set email alerts
|

Accidents involving pedestrians with their backs to traffic or facing traffic: an evaluation of crash characteristics and injuries

Abstract: SUMMARYThis paper examines pedestrian anatomical injuries and crash characteristics in back-to-traffic and facingtraffic crashes. Pedestrian crashes involving pedestrians walking along streets (i.e. with their backs to traffic or facing traffic) have been overlooked in literature. Although this is not the most frequent type of crash, the crash consequence to pedestrians is a safety concern. Combining Taiwan A1A2 police-reported accident data and data from the National Health Insurance Database from years 2003-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Studies have reported that facing traffic is beneficial for preventing pedestrian crashes27 and reducing the severity of related injuries 25. Our study complements these studies by concluding that walking against traffic is associated with decreased injury severity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Studies have reported that facing traffic is beneficial for preventing pedestrian crashes27 and reducing the severity of related injuries 25. Our study complements these studies by concluding that walking against traffic is associated with decreased injury severity.…”
Section: Discussionsupporting
confidence: 79%
“…Considerable work has concluded that older pedestrians are more likely to be fatally or severely injured in crashes, both during daytime and night conditions 25. Our research provides ample evidence to suggest that injuries sustained by older pedestrians in crashes caused by sun glare are more likely to be fatal than those sustained by younger pedestrians.…”
Section: Discussionmentioning
confidence: 56%
“…A thorough description of the National Traffic Accident Dataset can be found in the study by Chen et al . 22 …”
Section: Methodsmentioning
confidence: 99%
“…After a road traffic accident is made known to the police, certified police accident investigators examine the accident scene and complete accident reports, which comprise information relevant to the MVC. 11 The NHI data were retrieved from Taiwan’s NHI programme, which is implemented and supervised by the National Health Insurance Administration that also performs quarterly expert reviews on random samples of medical claims to ensure the accuracy of such claims. 12 This study was approved by the Institutional Review Board of National Cheng Kung University Hospital (No.…”
Section: Methodsmentioning
confidence: 99%